VIETNAMESE NATIONAL COSTUMES IN INTERNATIONAL BEAUTY PAGEANTS: SYMBOLS OF HERITAGE AND CULTURAL IDENTITY - Tram, Oanh Thi Trach (Jurnal Kajian Seni, 2026)
This article examines Vietnamese national costumes in international beauty pageants as collaborative creative achievements through which designers and contestants jointly communicate cultural heritage and national identity to global audiences. Drawing on a qualitative descriptive approach with visual analysis, the study surveys Vietnamese national costume design at three major international competitions - Miss Universe, Miss World, and Miss Grand International - between 2014 and 2024, and examines four outstanding designs in depth: “Ngu Phung Te Phi” (2018), “Ken Em” (2020), “Chieu Ca Mau” (2022), and “Vu Khuc Thien Long” (2023). These four cases were selected to represent a range of cultural referents, design approaches, and forms of international recognition, all sharing a common thread: each is built on the ao dai as a foundational form, extended through specific Vietnamese cultural symbols and living craft traditions. Analysis finds that successful Vietnamese national costume designs consistently demonstrate three interlocking principles: deep grounding in identifiable Vietnamese cultural symbols; technical mastery that elevates traditional craft to contemporary design; and communicative clarity that makes cultural meaning legible to diverse international audiences. The findings affirm that Vietnamese national costume design is a sustained field of cultural creativity in which innovation and tradition mutually reinforce one another